(11p-7q-r)+(3p+q-9r)+(-p-q+2r)=0

Simple and best practice solution for (11p-7q-r)+(3p+q-9r)+(-p-q+2r)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (11p-7q-r)+(3p+q-9r)+(-p-q+2r)=0 equation:


Simplifying
(11p + -7q + -1r) + (3p + q + -9r) + (-1p + -1q + 2r) = 0

Remove parenthesis around (11p + -7q + -1r)
11p + -7q + -1r + (3p + q + -9r) + (-1p + -1q + 2r) = 0

Remove parenthesis around (3p + q + -9r)
11p + -7q + -1r + 3p + q + -9r + (-1p + -1q + 2r) = 0

Remove parenthesis around (-1p + -1q + 2r)
11p + -7q + -1r + 3p + q + -9r + -1p + -1q + 2r = 0

Reorder the terms:
11p + 3p + -1p + -7q + q + -1q + -1r + -9r + 2r = 0

Combine like terms: 11p + 3p = 14p
14p + -1p + -7q + q + -1q + -1r + -9r + 2r = 0

Combine like terms: 14p + -1p = 13p
13p + -7q + q + -1q + -1r + -9r + 2r = 0

Combine like terms: -7q + q = -6q
13p + -6q + -1q + -1r + -9r + 2r = 0

Combine like terms: -6q + -1q = -7q
13p + -7q + -1r + -9r + 2r = 0

Combine like terms: -1r + -9r = -10r
13p + -7q + -10r + 2r = 0

Combine like terms: -10r + 2r = -8r
13p + -7q + -8r = 0

Solving
13p + -7q + -8r = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '7q' to each side of the equation.
13p + -7q + 7q + -8r = 0 + 7q

Combine like terms: -7q + 7q = 0
13p + 0 + -8r = 0 + 7q
13p + -8r = 0 + 7q
Remove the zero:
13p + -8r = 7q

Add '8r' to each side of the equation.
13p + -8r + 8r = 7q + 8r

Combine like terms: -8r + 8r = 0
13p + 0 = 7q + 8r
13p = 7q + 8r

Divide each side by '13'.
p = 0.5384615385q + 0.6153846154r

Simplifying
p = 0.5384615385q + 0.6153846154r

See similar equations:

| (-15-2)(-20)= | | 4x-2(x-3)=-8+5x-1 | | B*2A=bh | | 5+10=120 | | 13-(7-5*4)= | | (16x^2y^3z)/(-8x^3y^2z)=0 | | (6a^2b)*(14a^3b^2)=0 | | 9n-2-8n-15=-5 | | -200=250 | | -4(5)+5y=-15 | | d+10=30 | | -4x+5(3x-14)=-15 | | (x-2)/3=(x+7)/6 | | -5x+3(2)=-9 | | -5(-3+3y)+3y=-9 | | y-3x=2 | | -(-6x+z)+(y+4)=0 | | 1/2(5x-3)=8 | | 5-9x=3x-8x-27 | | 2(5)-13=y | | 3(5)+2(2(5)-13)=9 | | 8x^3-3x^2-36x+9=0 | | .50(5x-3)=8 | | (y-7)-(y+4)=4y | | 11x+5x=80 | | 3x+2(2x-13)=9 | | -7x-9=-93 | | Y=500+40x-x^2 | | (x+1)(x-4)= | | 17-4x/12=5 | | 20-6xn=10 | | 21/(y-8)=3 |

Equations solver categories